Uma visão ampliada sobre os jatos de baixos níveis na América do Sul - Kannenberg, Carolina (2019)
Recently, Oliveira, Nascimento and Kannenberg (2018) [ONK18] showed that the criteria employed in algorithms that identify low level jet (LLJ) traditionally used in South America fail to detect an important number of these events. Using the algorithm ONK18 to identify LLJs, this study presents a new climatology of LLJs in north quarter of South America using CFSR-CFSv2 Reanalysis data between 1980 and 2017. South American regions with higher occurrence of LLJs are indicated and compared with previous records in the literature. The seasonal variability and diurnal cycle of LLJs as well basics statistics of speed, high and direction of LLJ are analyzed in key regions. It is also investigated the sensibility of some results to different algorithms of LLJ detection and to different data sources. For this, the original algorithms of Bonner (1968) and Salio, Nicolini and Saulo (2002) are also used, and the ERA-interim data of 1980-2017 period and the rawindsondes of La Plata Basin between 1996-2015. The mean synoptic patterns associated with the occurrence of more intense LLJ in different regions are also presented. The results show that the criteria proposed by ONK18 detects a greater diversity of LLJs than the traditional criterias. The regimes of direction, height, magnitude of LLJ as well its seasonal and hourly variability vary with the geographic location. In mid and subtropical latitudes of the continent LLJ episodes have a latitudinal variation throughout the year, occurring more frequently in lower latitudes on Winter months and in higher latitudes during the Summer. Thus, transient baroclinc systems modulate the frequency and geographic location of the LLJs. The mean anomalies of synoptic fields during intense LLJs events in Santa Cruz de La Sierra (SCLS), Foz do Iguaçu e Santa Maria and Córdoba show that these LLJ are often located in a pre-frontal sector. This way, the LLJs more elevated in Santa Maria and Foz do Iguaçu tend to present a more oriented zone compared with Córdoba and Santa Cruz de La Sierra. In Santa Maria the easterly LLJs are lower and observed in a post-frontal environment, besides having a probable topographic forcing; in Rio de Janeiro coast, the LLJs are embedded in environments that seem to include pre-frontal but also Oceanics South Atlantic Convergence Zones (SACZ). In the north of Pará episodes of LLJs are almost exclusively from the east, what associate them with the incursion of the trade winds.